Changes in Soil Physical Properties Following Applications of Vermicompost Superimposed with Liquid Organic Fertilizer - Bandi Hermawan; Zainal Muktamar; Fahrurrozi Fahrurrozi; Nanik Setyowati; Sigit Sujatmiko; Muhammad Chosin; Elsa Lolita Putri (UNIVERSITY OF LAMPUNG, 2024)
Soil properties play essential roles in transmitting and holding precipitation water; therefore, they determine the amount of plant-available water in the soil profile. The study aimed to compare the size distributions of Andept soil pores following four-year applications of vermicompost and liquid organic fertilizer (LOF). The experiment was done from 2016 to 2019. The five doses of vermicompost (5, 10, 15, 20, and 25 Mg ha-1) set as the main factor, supplemented with 0 and 100 percent concentrations of LOF as a sub-factor, were arranged in a split-plot design with three replicates. Results showed that adding LOF decreased slow-drainage pores significantly when combined with 10 Mg ha-1 of vermicompost. However, the pore changes by LOF were not significant when applied to other doses of vermicompost. Applying vermicompost and LOF lowered the slow-drainage pores by increasing soil organic carbon and reducing soil particle density. The findings suggest that vermicompost and LOF act as soil ameliorants to reduce water loss by drainage from soil profiles. The study highlights the importance of soil properties in determining plant-available water in the soil profile.